2015
DOI: 10.1017/ice.2014.80
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Fecal Microbiota Transplantation for Recurrent Clostridium difficile Infection

Abstract: Our results suggest that FMT may be a cost-saving intervention in managing RCDI. Implementation of FMT for RCDI may help decrease the economic burden to the healthcare system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 42 publications
2
66
0
1
Order By: Relevance
“…Similar results have been demonstrated by other economic analyses evaluating FMT for treatment of recurrent CDI [10,14,15]. A cost-effectiveness analysis of strategies for treatment of recurrent CDI performed from a societal perspective in the USA concluded that FMT via colonoscopy was cost-effective with an ICER of $17,016 compared with vancomycin at a willingness-to-pay threshold of $50,000/QALY [10].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Similar results have been demonstrated by other economic analyses evaluating FMT for treatment of recurrent CDI [10,14,15]. A cost-effectiveness analysis of strategies for treatment of recurrent CDI performed from a societal perspective in the USA concluded that FMT via colonoscopy was cost-effective with an ICER of $17,016 compared with vancomycin at a willingness-to-pay threshold of $50,000/QALY [10].…”
Section: Discussionsupporting
confidence: 75%
“…Another study by Varier et al compared vancomycin with FMT for recurrent CDI from a third-party payer perspective using U.S. data. Even though the authors accounted for adverse events of colonoscopy, they found that FMT administered via colonoscopy was both less costly and more effective than prolonged oral vancomycin taper at all willingness-to-pay thresholds based on the probabilistic sensitivity analysis [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Although excluding costs of treatment-related adverse events would bias results, only 3 studies included such costs. 15,16,31 Most studies used official sources for cost estimates, and US studies had higher per-unit costs than studies in other countries. The cost of FMT therapy varied depending on the route of administration and often included associated pretreatment cost of oral vancomycin.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Due to the rising prevalence, severity and mortality of this infection, the therapeutic role played by FMT is therefore important to save human lives and to decrease the economic burden on healthcare systems. [8][9][10][11] Based on these data, both the European Society for Microbiology and Infectious Disease and the American College of Gastroenterology recommend FMT as a treatment for rCDI. 12 13 Beyond the treatment of CDI, FMT has also been investigated in other disorders associated with the alteration of gut microbiota.…”
Section: Introductionmentioning
confidence: 99%